Familial autosomal dominant severe ankyloglossia with tooth abnormalities. Issue 7 (28th April 2018) - Lenormand, Anaëlle; Khonsari, Roman; Corre, Pierre; Perrin, Jean Philippe; Boscher, Cécile; Nizon, Mathilde; Pichon, Olivier; David, Albert; Le Caignec, Cedric; Bertin, Helios; Isidor, Bertrand
Abstract : Ankyloglossia is a congenital oral anomaly characterized by the presence of a hypertrophic and short lingual frenulum. Mutations in the gene encoding the transcription factor TBX22 have been involved in isolated ankyloglossia and X‐linked cleft palate. The knockout of Lgr5 in mice results in ankyloglossia. Here, we report a five‐generation family including patients with severe ankyloglossia and missing lower central incisors. Two members of this family also exhibited congenital anorectal malformations. In this report, male‐to‐male transmission was in favor of an autosomal dominant inheritance, which allowed us to exclude the X‐linked TBX22 gene. Linkage analysis using short tandem repeat markers located in the vicinity of LGR5 excluded this gene as a potential candidate. These results indicate genetic heterogeneity for ankyloglossia. Further investigations with additional families are required in order to identify novel candidate genes.